Striatal prediction errors support dynamic control of declarative memory decisions - Jason M. Scimeca (Nature Portfolio, 2016)
The human brain can efficiently retrieve information from long-term memory and use it to guide action but how the brain selects the most useful information in each case is unclear. Here the authors show that reinforcement learning mechanisms, based on expected value and prediction error fMRI signals in striatum, play a role in memory control processes guiding behavior.